Answers

2014-11-13T20:26:26+08:00
Let 'x' be the age of Cita at present
      'y' be the age of Bona at present
      'z' be the age of Albert at present
------------------------------------------------
Four years from now:
x+4  ---Cita's age
y+4  ---Bona's age
z+4  ---Albert's age
-------------------------------------------------
Translating the statements into mathematical expressions you'll have:
x = y + 6     ----equation 1
y = 2z         ----equation 2
(x+4) = (y+4) +(z+4) - 8     -----equation 3
From equation 3
(x+4) = (y+4) +(z+4) - 8
x + 4 = y + 4 + z + 4 - 8
x + 4 = y + z     -----equation 3'
Express x and z in terms of y
From equation 2
y = 2z
z = y/2   ----equation 2'
Substitute equations 2' and equation 1 to equation 3'
x + 4 = y + z
(y+6) + 4 = y + y/2
y + 6 + 4 = y + y/2
Combine like terms
y - y + y/2 = 10
y/2 = 10
Cross multiply
y = 20 yrs old ----Bona's age
Substitute y=20 to equation 2
y = 2z
20 = 2z
z = 20/2
z = 10  ----Albert's age
substitute y=20 to equation 1
x = y + 6
x = 20 + 6
x = 26 yrs old ---Cita's age
0